2021
DOI: 10.1021/acsomega.1c01473
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Framework of Zinc-Decorated Inorganic Mg12O12 Nanoclusters for Efficient COCl2 Adsorption: A Step Forward toward the Development of COCl2 Sensing Materials

Abstract: Gas sensors are widely explored due to their remarkable detection efficiency for pollutants. Phosgene is a toxic gas and its high concentration in the environment causes some serious health problems like swollen throat, a change in voice, late response of nervous systems, and many more. Therefore, the development of sensors for quick monitoring of COCl 2 in the environment is the need of the time. In this aspect, we have explored the adsorption behavior of late transition metal-decorated Mg 12 O 12 nanocluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…They were calculated using Koopmans’ approximation and are shown in Table . The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO), often known for molecular descriptive energy gap computation, provide information on a compound’s electrical, optical, and biological reactivity characteristics and stability. More chemical reactivity and simpler electron transitions from the HOMO to the LUMO are associated with a smaller energy difference or gap. A larger energy gap indicates more chemical stability, which influences how easily electrons may be transported from HOMO to LUMO.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were calculated using Koopmans’ approximation and are shown in Table . The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO), often known for molecular descriptive energy gap computation, provide information on a compound’s electrical, optical, and biological reactivity characteristics and stability. More chemical reactivity and simpler electron transitions from the HOMO to the LUMO are associated with a smaller energy difference or gap. A larger energy gap indicates more chemical stability, which influences how easily electrons may be transported from HOMO to LUMO.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It can be observed that carboplatin prefers to interact with the cationic sites of the sorbent via its O head. It is apparent from the obtained results that the E ads values for all interactions are negative, which indicates that there is a strong interaction between the doped clusters and carboplatin. Thus, the type of adsorption that exists is chemisorption. Furthermore, doping AlN clusters with Na, Mg, and K causes a considerable change in the Δ E g of the surface, which also in turn affected the adsorption energies of the drug considerably.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The density of states plots have been utilized to further give insight into the charge density transfer arising from intermolecular interactions of the gases with the nanostructured surface. Partial density of states (PDOS) explicates the contributions of individual atomic and molecular orbitals to distinct quantum states in the studied nanostructured materials . The conductivities of the surfaces are also revealed from the DOS plots more explicitly.…”
Section: Resultsmentioning
confidence: 99%
“…Commonly, 4000–600 cm −1 is the range in which experimental FT‐IR spectrum most of the time is recorded, and theoretical spectrum with harmonic frequencies, intensities of the vibrational bands, and nature of vibrational modes for compounds 1 – 16 were examined by utilizing DFT/B3LYP/6‐31G(d,p) level of theory. [ 48,87,94–100 ] Tables 7–10 enclose the important theoretical and experimental FT‐IR descriptions along with the mode of vibrations.…”
Section: Resultsmentioning
confidence: 99%